The Importance of Competence (Education) at Pt. Banjarmasin Main Vistra - Widarto; Aulia Nurani Savitri; Rizalul Gadi; Riky Welli Saputra (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine the competence of Human Resources at PT. Main Vistra, to find out the obstacles faced in fulfilling employee competencies and the efforts or alternative solutions faced. To obtain valid data in research using descriptive methods. Data collection techniques using documentation, observation, and interviews, with qualitative data analysis techniques. The results of the study show that the human resource competencies at PT. Vistra Utama started with the recruitment process, which included administrative tests, written selection, and interviews, then continued with placement and development. Furthermore, the efforts made or alternative solutions that need to be made related to increasing competence are the need for cooperation with associations in the field of martial arts within the Banjarmasin City community in terms of recruiting prospective outsourced employees, carrying out the On The Job Training and briefings held by PT Vistra Utama and Conduct work evaluation every six months or once a year.